2021
DOI: 10.1186/s12879-021-06064-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of neutrophil CD64, procalcitonin, and interleukin-6 in sepsis: a meta-analysis

Abstract: Background The aim of the study was to conduct a meta-analysis to evaluate the accuracy of neutrophil CD64, procalcitonin (PCT), and interleukin-6 (IL-6) as markers for the diagnosis of sepsis in adult patients. Methods Various databases were searched to collect published studies on the diagnosis of sepsis in adult patients using neutrophil CD64, PCT, and IL-6 levels. Utilizing the Stata SE 15.0 software, forest plots and the area under the summary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…However, a wide variation in the performance of CD64 can be observed, depending on the study design. In 2021, Cong et al compiled 20 studies and found that the pooled sensitivity and specificity were 0.88 (95% CI 0.81–0.92) and 0.88 (95% CI 0.83–0.91), respectively 68 . Our results suggest that CD64 has > 80% specificity, but its sensitivity is modest (70%) in distinguishing infectious from noninfectious patients and even low (59%) in discriminating localized versus systemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, a wide variation in the performance of CD64 can be observed, depending on the study design. In 2021, Cong et al compiled 20 studies and found that the pooled sensitivity and specificity were 0.88 (95% CI 0.81–0.92) and 0.88 (95% CI 0.83–0.91), respectively 68 . Our results suggest that CD64 has > 80% specificity, but its sensitivity is modest (70%) in distinguishing infectious from noninfectious patients and even low (59%) in discriminating localized versus systemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several clinical scores were evaluated for their ability to recognize patients at higher risk of death, but a recent systematic review and meta-analysis suggested that Early Warning Scores and qSOFA not always predict mortality accurately in patients with sepsis [ 29 , 30 ]. In addition, many studies in the literature tested the independent value of biochemical markers for their ability to predict sepsis, without conclusive results, leaving clinicians in the need of further aid [ 31 34 ]. The evaluation of specific subsets of peripheral immune cells may, indeed, improve current prediction models to timely recognize septic patients at higher risk of poor outcome, taking into account the immunological status at onset of sepsis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD64 is an IgG-binding receptor expressed by neutrophils, monocytes, and macrophages in response to cytokines released during bacterial infection; given that its expression is upregulated in the early stages of activation of the innate immune response, it performs particularly well as a diagnostic marker of sepsis [ 122 ], although its use might be limited by flow cytometry, the method used for CD64 detection, requiring specialized laboratory equipment.…”
Section: Diagnosis Of Sepsismentioning
confidence: 99%